Using mother tongue as a medium of instruction in the teaching of mathematics in the Zimbabwean junior primary schools: Desirable or feasible? - Mufanechiya, Albert; Mufanechiya, Tafara (Journal of Asian Scientific Research, 2011)
The use of mother tongue as a medium of instruction debate has been on the cards for a long time now in Zimbabwe but has never had any genuine implementation commitment from the policy makers. The study focuses on language use and challenges teachers and pupils face in the classroom in their attempt to use mother tongue in the teaching and learning of mathematics at junior primary level. The study sample comprised 32 teachers from Masvingo urban primary schools, 32 of their lessons were observed and learners from these classes participated in the study. Observation protocol and a structured questionnaire were the data collection instruments. The research found out that the use of mother tongue in teaching mathematics may not be achieved soon. Consultations with relevant stakeholders, attitude change and resource production and mobilisation are among some of the many issues militating against the use of mother tongue as a medium of instruction in mathematics. One of the major recommendation was to have an all stakeholder conference, comprising politicians, academics , language experts, representatives from countries where mother tongue tuition has been successfully implemented in educational settings; teachers and parents to openly debate the feasibility of using mother tongue as a medium of instruction in education in general. Mathematics would obviously benefit from such a conference.